Russia and Central Asia: History and Present of Economic Relations (International relations and international law Journal, 2019)
Abstract. After the collapse of the Soviet Union, the relationships of Russia and the countries of CentralAsia are saturated with different events. What have been and what will be the effects of this? In an attemptto answer this complex question, it is necessary to assess the situation in one of the most importantspheres of the relations – economics. The uniqueness of the ongoing research since 2003 (Paramonov,2004), which serves as the basis for this article lies within a systematic evaluation of the key elementsof interaction between Russia and Central Asian countries in political, security, economic (including theenergy sector), as well as social spheres. Through this prism, the most important factors and stages ofthe relations in the period 1991–2018 are indicated. The article also provides some important statisticalinformation which has not been combined in one material before. The article aims at identifying andcomparing the main elements in relationships between Russia and countries of Central Asia. An interdisciplinaryapproach with the methods of dialectic and structural-functional analysis has been used toachieve this goal. The relevance of the article lies within the growing influence of numerous factors (bothexternal and internal) due to which Central Asia is becoming one of the most important geo-economicand geopolitical regions for Russia. Furthermore, the situation in Central Asia is also changing more rapidly and dynamically. Primarily, it is related to the continued activation of the regional and internationalpolicies of Uzbekistan. The article concludes that economic relations can be characterized by certainpositive dynamics. Nevertheless, it is still too early to talk about the long-term trends and significant successin Russian – Central Asian relations.Key words: Russia, Central Asia, Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, Uzbekistan, politics,economy, trade, investments, labor migration.